1998
DOI: 10.1177/074171369804800204
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Role Conflict, Overload and Contagion in Adult Women University Students with Families and Jobs

Abstract: Many adult women studying at universities face difficulties related to their multiple roles, yet little is known about vulnerable groups or supportive responses. This study of 443 women with jobs and families enrolled in adult education, social work, or nursing identified to what extent life situations, institutional supports, and perceived demands and support systems predict role conflict, overload, and contagion. Multiple regression analysis was used to identify predictors. Income was the only life situation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
126
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(131 citation statements)
references
References 22 publications
4
126
0
1
Order By: Relevance
“…As identified in earlier research (Home, 1998), juggling domestic, paid work and study responsibilities created significant tension for the women we interviewed. Most of the students also talked about the additional financial burden experienced as a result of undertaking placement.…”
Section: Feeling Over-burdenedmentioning
confidence: 96%
See 2 more Smart Citations
“…As identified in earlier research (Home, 1998), juggling domestic, paid work and study responsibilities created significant tension for the women we interviewed. Most of the students also talked about the additional financial burden experienced as a result of undertaking placement.…”
Section: Feeling Over-burdenedmentioning
confidence: 96%
“…In addition to cutting back on paid employment, six students in our cohort mentioned they also had key care giving responsibilities for dependent children. Previous research on the experience of mature aged students re-entering education (Osborne et al, 2004;Home, 1998) reported stressors related to the cost of the course and additional childcare while juggling the competing demands on time.…”
Section: Feeling Over-burdenedmentioning
confidence: 99%
See 1 more Smart Citation
“…The marital status coefficient was expected to be a negative value. With regard to family status, the empirical findings of Beutell and Greenhaus (1982) and Home (1998) indicated that employees who have children younger than six years old are unable to simultaneously dedicate full attention to both family and work, and this affects their work performance. Since small children rely on family for nurturing and upbringing, more time and effort is required to care for them, which affects an employee's working hours and performance.…”
Section: Variable Definition and Explanationmentioning
confidence: 99%
“…Home (1998) revealed that their lower income increased their vulnerability to role conflict, overload and contagion. And Atack and Rankin (2002) explained that having access to computers for course work in health care settings can be problematic.…”
Section: Situating Lpn To Bn Students As Adult Women Entering Online mentioning
confidence: 99%